State Policy in the Tourism Field of Ukraine: Socio-Humanitarian Priorities of Development and Post-War Recovery - Olha Petroye (Культура і мистецтво у сучасному світі)
In the reviewed monograph “State policy in the tourism field of Ukraine: socio-humanitarian dimension”, the author Alla Havryliuk offers to use the marketing paradigm of promoting domestic tourism as a national ideology, as well as a tool of management and territory development. New directions of state policy implementation in conditions of decentralisation, focused on promoting key tourist identifiers of the locality are presented, such as types of tourism, image, brand, reputation, souvenir branding and intangible cultural heritage.